2019
DOI: 10.1161/circgen.118.002413
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Receptor Signaling and Abdominal Aortic Aneurysm Growth Rates

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 46 publications
1
42
0
1
Order By: Relevance
“…The discovery that the pro-inflammatory activities of IL-6 are mediated by IL-6 trans-signalling whereas the protective and regenerative activities of IL-6 rely on classic signalling via the membrane-bound IL-6R suggested that the sgp130Fc protein might be an ideal candidate for a more specific mode of cytokine blockade as opposed to global cytokine inhibition 20 . It was shown in appropriate animal models that blockade of IL-6 trans-signalling was indeed superior to global IL-6 blockade in a bone healing model 44,45 , in a sepsis model 42 , in abdominal aortic aneurysm models 43 , and in bacterial infection models 40,41 . The sgp130Fc protein was expressed and purified according to GMP regulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery that the pro-inflammatory activities of IL-6 are mediated by IL-6 trans-signalling whereas the protective and regenerative activities of IL-6 rely on classic signalling via the membrane-bound IL-6R suggested that the sgp130Fc protein might be an ideal candidate for a more specific mode of cytokine blockade as opposed to global cytokine inhibition 20 . It was shown in appropriate animal models that blockade of IL-6 trans-signalling was indeed superior to global IL-6 blockade in a bone healing model 44,45 , in a sepsis model 42 , in abdominal aortic aneurysm models 43 , and in bacterial infection models 40,41 . The sgp130Fc protein was expressed and purified according to GMP regulations.…”
Section: Discussionmentioning
confidence: 99%
“…With the help of the sgp130Fc protein and of neutralising monoclonal antibodies, it was possible to selectively block IL-6 trans-signalling or to block all IL-6 signalling, respectively. Using this approach, it was shown that classic IL-6 signalling via the membrane-bound IL-6R was responsible for the defence of the body against bacteria 40 , 41 , intestinal regeneration upon polymicrobial sepsis 42 , prevention of aortic rupture in animal models of abdominal aortic aneurysm 43 , and healing of bone fractures 44 , 45 , indicating that these important processes are severely compromised under blockade of global IL-6 activity 46 . It has been hypothesised that the same might apply for the treatment of COVID-19 patients 46 ( Figure 4 ).…”
Section: Physiologic and Pathophysiologic Functions Of Interleukin-6mentioning
confidence: 99%
“…In our study, sgp130 displayed a non-linear association and in previous observational studies, sgp130 has been associated with both protective and detrimental properties (114,151,153,154). While administering supra-physiological doses of recombinant sgp130Fc resulted in dampened atherosclerosis and fewer ruptures of abdominal aortic aneurysms in two murine models of atherosclerosis (138,140). Considering the above, physiological sgp130 levels possibly mirrors the activity in the pathway rather than the level of IL6 trans-signalling inhibition.…”
Section: Study Imentioning
confidence: 98%
“…Moreover, patients with the rs2228145 SNP showed a significant lower risk of Crohn’s disease and ulcerative colitis as compared to control individuals [29]. Furthermore, growth rates of abdominal aortic aneurisms in patients were smaller with the Ala358 variant of the IL-6R [30]. These results can be explained by a higher capacity of the IL-6 buffer in the blood, which is caused by the higher circulating sIL-6R levels [20,23].…”
Section: Introductionmentioning
confidence: 99%